1966
DOI: 10.1063/1.1708259
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Resistivity at Interfaces between Metal and Dielectric Films at 1.5° to 4.2°K

Abstract: Measurements of the thermal resistivity at interfaces between metal and dielectric thin films and a bulk substrate are reported. The thin-film structures are representative of a variety of superconducting devices with electrically insulated components. Results were obtained for single and multiple layers from 1.5° to 4.2°K. The magnitude of the observed values are within the range of the Little formulation if only longitudinal phonon contribution is considered. The temperature dependence is approximately T−2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…For example it was shown in Ref. 25 that the thermal conductance is sensitive to the quality of adhesion of the film to the substrate; it was suggested that an imperfect bond may be able to allow the transmission of heat only via longitudinal waves. In view of the crude nature of these calculations, it is believed that the agreement between theory and experiment is certainly good enough to draw simple conclusions concerning the appropriate application of particular materials for use as substrate materials.…”
Section: Thermal Boundary Resistancementioning
confidence: 99%
“…For example it was shown in Ref. 25 that the thermal conductance is sensitive to the quality of adhesion of the film to the substrate; it was suggested that an imperfect bond may be able to allow the transmission of heat only via longitudinal waves. In view of the crude nature of these calculations, it is believed that the agreement between theory and experiment is certainly good enough to draw simple conclusions concerning the appropriate application of particular materials for use as substrate materials.…”
Section: Thermal Boundary Resistancementioning
confidence: 99%
“…In measurement #2 we measured the I-V characteristic of a device mounted in a vacuum dewar, like it would be used in an astronomical receiver. In this case the significantly smaller Kapitza conductance between Au and SiO 2 results in a stronger heating effect than one would obtain for the same measurement with the device immersed in a LHe vessel where the Kapitza conductance is three times larger (values for the Kapitza resistances we used can be found in [13,14]). In Fig.…”
Section: Experiments and Measurement Resultsmentioning
confidence: 78%
“…The third fit parameter is the heat transfer coefficient ho which is a measure of the thermal coupling evaluated heat-transfer coefticient by Holt [35]. Figure 17 are most likely due to the fact that we assumed a temperature apparently smaller than the theoretical value.…”
Section: Experimental Results 1 9 O C R O U T P U T Inmentioning
confidence: 99%